The Concept of Wage in Contemporary Economic Systems: The Garments Industry’s Wage Structure and Social Issues - Balbin, Remedios C. (Philippine Management Review; Vol 2 (1991), 2016)
This article discusses some ideological and historical concepts of wage under various economic systems.  It looks at the garments industry in the Philippines as a model for analyzing the impact of the wage structure on industrial performance and on the achievement of a “just” a “living wage.”  Wage setting practices are examined and related to productivity under various conditions of production arrangements.  In particular, subcontracting as an operation common in the garments industry is cited to illustrate the dilemma of achieving productivity at the same time with just and equitable wage.  What appropriate government policies then need to be formulated, for the garments industry? For other industries? This is the key question being asked and attempted to be answered in this article.